Disclosing Professionalism Behaviour of Internal Auditor in Preventing Fraud By Using the Local Cultural Wisdom ‘Longko’ (A Case Study at Toraja Tribe, South Sulawesi, Indonesia) - Paranoan, N; Peleng Roreng, P; Jeane Tandirerung, C; Sadesto Tandungan, E (KnE Social Sciences, 2018)
This study aims to disclose the behaviour of professionalism displayed by internal auditors in preventing fraud by using local wisdom and the values of the Torajanese culture, namely longko’. This study was conducted using the qualitative method of ethnomethodology. The professional behaviour of the internal auditors is measured by using dimensions: dedication in profession, social obligations, personal autonomy demands, belief in self-regulation of profession and community affiliation. The longko’ culture was analysed with the dimension of kamalamburan (honesty) and the dimension of karapasan (harmony), two values that are prioritised and preferred by the Torajanese community. The results of this study were interpreted and revealed that internalising the longko’ culture will control the internal auditor’s professional behaviour in fraud prevention and generate a concept of professionalism for the internal auditor based on Torajanese culture in order to achieve a clean organisational governance from fraud. Keywords: professionalism, internal auditor, fraud, Longko’